Основи безпеки занять фізичними вправами: страхування та самострахування - Візавер Вікторія; Vizáver Viktória; Viktoriia Vyzaver; Візавер Арпад; Vizáver Árpád; Arpad Vyzaver; Рошинець Тімея; Roshinets Timeya (Видавництво «Код», 2025)
Резюме. У статті розкрито сутність поняття «основи безпеки», окреслено шляхи формування необхідних навичок у студентів ЗВО щодо дотримання вимог техніки безпеки під час занять фізичними вправами. Розглянуто професійну майстерність викладача у наданні необхідної інформації для студентів по попередженню нещасних випадків під час занять фізичними вправами у самостійних заняттях.

Abstract. The main task of training future specialists is the formation and improvement of professional competencies capable of determining, designing, organizing and modeling the educational process. An important component in this process is caring for the health of those who are engaged in physical culture and sports. It is the prevention of injuries that is considered an integral part of the educational process. This allows the teacher to promote a healthy lifestyle, helps the student to understand the patterns of health formation, and lead a healthy lifestyle. The urgency of this problem is due to the increase in accidents during sports activities and sports competitions. This situation requires specialists to find new, more effective ways to increase the safety of student youth, to raise health and preventive measures to a higher level. The article reveals the essence of the concept of "safety basics" and outlines ways to form the necessary skills in students of higher education institutions regarding compliance with safety requirements during physical exercise. The professional skills of the teacher in providing the necessary information to students on the prevention of accidents during physical exercises in independent classes are considered. Having studied the issue of the state of students’ awareness of the basics of safety during physical education and sports, both organized and independent, we can confidently say that this problem exists, but it must be approached more responsibly, taking appropriate measures, and implementing the latest health-saving technologies. Thus, physical education teachers need to take this situation into account, despite the fact that direct contact with students has significantly decreased, find an opportunity to bring the necessary information on safety techniques during physical education classes to students, and provide them with knowledge, skills, and abilities that will significantly affect this situation. Physical education leaders must teach students the skills of insurance and self-insurance, this is one of the most important elements, especially during independent classes. Insurance is presented as a set of measures aimed at ensuring the safety of those involved in physical education and sports, and self-insurance is presented as the ability to independently get out of difficult, dangerous situations by stopping the exercise or changing it in order to prevent injuries.
Basic safety in physical exercise: insurance and self-insurance
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-16?authuser=0
Keywords: техніка безпеки; здоров’язбережувальна діяльність; травми; профілактика травматизму; види травм; страхування; самострахування